Prognostic significance of DSG3 in rectal adenocarcinoma treated with preoperative chemoradiotherapy. (June 2016) - Chao, Tung-Bo; Li, Chien-Feng; Lin, Ching-Yih; Tian, Yu-Feng; Chang, I-Wei; Sheu, Ming-Jen; Lee, Ying-En; Chan, Ti-Chun; He, Hong-Lin
Aim: This study aimed to investigate the prognostic significance of DSG3 and its association with response to neoadjuvant concurrent chemoradiotherapy (CCRT) in rectal cancer.Materials & methods: Data mining of a publicly available dataset was performed to find genes associated with CCRT response. Immunohistochemistry was applied to evaluate DSG3 expression. The relationships between DSG3 expression and various clinicopathological parameters and survival were analyzed.Results: The DSG3 gene was significantly associated with CCRT response. The expression of DSG3 negatively correlated with poorer tumor regression (p < 0.001) and had an independent negative impact on disease-specific survival (p = 0.011), local recurrence-free survival (p = 0.031) and metastasis-free survival (p = 0.029).Conclusion: DSG3 was a key prognostic factor and predictor for CCRT response in rectal cancer patients.